Muñoz-Díaz, Javier; Ibacache, Kathia, and Gómez, Leila. (2024). Indigenous Materials in Libraries and the Curriculum. Latin American and Latinx Sources: London & New York: Routledge.ISBN: 978-1-032-61849-4 (hbk), 978-1-032-66061-5 (pbk), 978-1-032-66056-1 (ebk) - Ojeda, Jermani (2024)
Javier Muñoz-Díaz, Kathia Ibacache, and Leila Gómez—Latinx scholars based at U.S. universities—advocate for genuine decolonization, moving beyond what Tuck and Yang (2012) describe as merely “metaphorical” efforts. They emphasize the importance of integrating and promoting Indigenous literary materials within university libraries and curricula, which are still predominantly shaped by Eurocentric frameworks. Their approach aligns with Aymara scholar Rivera Cusicanqui’s (2012) call for decolonizing practice, which requires collaboration across multiple agents—Indigenous communities, Latinx scholars, librarians, faculty, and Indigenous content producers. This collective effort seeks to challenge how Indigenous peoples are often positioned within academia merely as instructors, informants, or cultural performers, thereby addressing the “geopolitics of knowledge” that maintains unequal power dynamics. They call for political collaboration grounded in the sovereignty and autonomy of Indigenous peoples, advocating for partnerships between Indigenous and non-Indigenous communities (Keme, 2018) to ensure that Indigenous knowledge systems and perspectives shape academic spaces on their own terms.